Being active when living within a large body: experiences during lifestyle intervention. Issue 1 (1st January 2020) - Toft, Bente Skovsby; Galvin, Kathleen; Nielsen, Claus Vinther; Uhrenfeldt, Lisbeth
ABSTRACT: Background : In-depth understanding of the experiences of both well-being and suffering in relation to being severely obese and becoming active through lifestyle intervention is lacking. Aim : to explore and describe adults' existential experiences of being active, when living within a large body—before and during a lifestyle intervention. Methods: A longitudinal design of repeated indivi dual interviews with 16 adults with BMI ≥40, based on hermeneutic phenomenology, existential philosophy and a theory of well-being was performed. The study was approved by the Danish health authorities. Results : Two dimensions of experiences were found; "Living within a downward spiral" and "Striving for enjoyment and settlement". The themes describing suffering were: 'Sense of being thwarted and defeated ' and "Tackling energy depletion and impact of sense of self". The themes describing well-being were: "Hoping for renewal and energised resoluteness" and "Enduring discomfort and feeling safe". Conclusions : Interacting existential experiences can be facilitators or barriers for physical activity. It seems relevant for health care providers to address the individual's lifeworld experiences of well-being, lack of well-being and suffering. Well-being as a sense of feeling "at home" when physically active may break down an inactivity spiral. Promoting well-being is a legitimate aim of lifestyle intervention.